PENGUATAN KOMPETENSI GURU DALAM PENULISAN ARTIKEL ILMIAH DI SEKOLAH MUTIARA HARAPAN PANGKALAN KERINCI RIAU - Mulyadi, Yadi; Suang, Lei; Miyondri, Popi (Faculty of Language and Literature Education, Universitas Pendidikan Indonesia, 2023)
The era of the industrial revolution 4.0 encouraged the development of knowledge to be more rapid. The development of knowledge will also have an impact on the world of education. The teacher is the foremost person in education because the teacher is the person who interacts directly instilling competence in students. This workshop activity aims to improve the competency of writing scientific articles for teachers at the Mutiara Harapan School, Pangkalan Kerinci, Riau. The method used is the Participatory Action Research (PAR) method. This activity was carried out online for a period of 2 months. In its implementation, this activity uses four stages in providing assistance, namely the planning, action, observation, and reflection stages. The results of the mentoring show that teacher competence in writing scientific articles has increased. In the initial conditions, according to the interview results, teachers had poor competence in writing scientific articles. However, after implementing the training, teacher understanding increased and 10 scientific articles were produced which could be registered in the target journal. From its implementation, the webinar activity received a positive response and was needed by teachers in an effort to improve the competence of writing scientific articles.